2020
DOI: 10.1177/1120672120975331
|View full text |Cite
|
Sign up to set email alerts
|

Implementing the new normal in ophthalmology care beyond COVID-19

Abstract: The COVID-19 pandemic has altered the clinical landscape immeasurably. The need to physical distance requires rethinking how we deliver ophthalmic care. Within healthcare, we will need to focus our resources on the five T’s: Utilising technology, multidisciplinary clinical teams with wide professional talents need to work efficiently to reduce patient contact time. With regular testing, this will allow us to reduce the risk further. We also must acknowledge the explosion of different modalities to train our fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…We consider this result particularly remarkable now during COVID-19 pandemic, where Ophthalmologists are at high risk due to their proximity and short working distance at the time of slit-lamp examination, 17 and when contact time between healthcare professionals and patients' needs to be reduced. 18 On average, around 50 patients per day undergo IVI without over-crowding the IVIC and OT, which allows personnel to be redeployed for other OTs, and 72 slots for IVI are available for each daily session. These results are in line with a previous study, which also has shown an increase of the weekly number of slots for IVIs available and of weekly IVIs sessions.…”
Section: Discussionmentioning
confidence: 99%
“…We consider this result particularly remarkable now during COVID-19 pandemic, where Ophthalmologists are at high risk due to their proximity and short working distance at the time of slit-lamp examination, 17 and when contact time between healthcare professionals and patients' needs to be reduced. 18 On average, around 50 patients per day undergo IVI without over-crowding the IVIC and OT, which allows personnel to be redeployed for other OTs, and 72 slots for IVI are available for each daily session. These results are in line with a previous study, which also has shown an increase of the weekly number of slots for IVIs available and of weekly IVIs sessions.…”
Section: Discussionmentioning
confidence: 99%
“…As we are still trying to control the COVID-19 pandemic, adopting new strategies in patients' care like telemedicine, using fundus photography, and smartphone assisted slit-lamp examination instead of conventional methods has become essential. [32][33][34][35] Industrial incorporations of protective equipment like slit-lamp shields in the ophthalmic clinic settings should be implemented. Further studies regarding the real protective value of the currently used PPE are needed which could help with optimizing the PPE designs to obtain adequate protection with better compliance among healthcare workers.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the recent COVID-19 pandemic has created many hurdles for individuals seeking ophthalmic care. [ 3 4 5 ] Teleophthalmology solutions integrated with AI algorithms are able to reduce clinician review times by screening large numbers of batched image files for pathology. [ 6 ]…”
mentioning
confidence: 99%